Multilevel survival analysis of the age at first birth among women in Ethiopia - Hussen, Nuru Mohammed; Arega, Gezachew Gebeyehu; Shibeshi, Abdu Hailu; Habtie, Getnet Mamo; Kassa, Tigabu Hailu; Getaneh Arge, Kassaye (Frontiers in Reproductive Health, 2024)
IntroductionThe age at first birth refers to the age at which a woman has her first child. It can significantly influence the demographic behavior of women and the general community. Moreover, teenage childbearing is a serious public health and social problem. The main objective of this study was to identify factors associated with age at first birth among women in Ethiopia.MethodsSecondary data on women were obtained from the 2019 Ethiopia Mini Demographic and Health Survey (EMDHS). These population-based cross-sectional data were downloaded from the Measure Demographic and Health Survey website (http://www.measuredhs.com). The study included a random sample of 8,885 women aged 15–49 years from 305 enumeration areas. A multilevel survival analysis was employed to identify the factors associated with teenage childbearing among women in Ethiopia.ResultsThe majority (67.7%) of randomly sampled women were subjected to teenage childbearing. Women being rural dwellers [hazard ratio (HR) = 1.27, 95% CI: 1.05, 1.54]; women from middle-income families (HR = 1.43, 95% CI: 1.18, 1.74); and women from higher-income families (HR = 1.40, 95% CI: 1.15, 1.70) were associated with a higher risk of teenage childbearing. Conversely, contraception method users (HR = 0.87, 95% CI: 0.77, 0.99), Muslims (HR = 0.75, 95% CI: 0.64, 0.89), Orthodoxes (HR = 0.68, 95% CI: 0.57, 0.80), women with secondary education (HR = 0.53, 95% CI: 0.43, 0.65), women with higher education (HR = 0.28 (95% CI: 0.22, 0.37), and the higher age of household head (HR = 0.99, 95% CI: 0.98, 0.99) were associated with a lower risk of teenage childbearing among women in Ethiopia.ConclusionSince the median age of women to have their first child was 18 years old, this study strongly suggests that stakeholders at the federal and regional levels must work closely toward enforcing the legal age of marriage and implementing national adolescents’ and youths’ targeted sexual and reproductive health programs.